In vivo magnetic resonance imaging of the human limbic white matter - Mori, Susumu; Aggarwal, Manisha (Frontiers in Aging Neuroscience, 2014)
The limbic system mediates memory, behavior, and emotional output in the human brain, and is implicated in the pathology of Alzheimer’s disease and a wide spectrum of related neurological disorders. In vivo magnetic resonance imaging (MRI) of structural components comprising the limbic system and their interconnections via white matter pathways in the human brain has helped define current understanding of the limbic model based on the classical circuit proposed by Papez. MRI techniques, including diffusion MR imaging, provide a non-invasive method to characterize white matter tracts of the limbic system, and investigate pathological changes that affect these pathways in clinical settings. This review focuses on delineation of the anatomy of major limbic tracts in the human brain, namely, the cingulum, the fornix and fimbria, and the stria terminalis, based on in vivo MRI contrasts. The detailed morphology and intricate trajectories of these pathways that can be identified using relaxometry-based and diffusion-weighted MRI provide an important anatomical reference for evaluation of clinical disorders commonly associated with limbic pathology.